Work-Family Conflict, Task Interruptions, and Influence at Work Predict Musculoskeletal Pain in Operating Room Nurses - Marina Nützi; Patricia Koch; Heiner Baur; Achim Elfering (Elsevier, 2015)
Background: The aim of this study is to examine the prevalence of musculoskeletal complaints in Swiss operating room (OR) nurses, and to investigate how work-family conflict, work interruptions, and influence at work are related to lumbar and cervical back pain. Methods: Participants in this correlational questionnaire study included 116 OR nurses from eight different hospitals in Switzerland. Results: We found that 66% of the OR staff suffered from musculoskeletal problems. The most prevalent musculoskeletal complaints were lumbar (52.7%) and cervical pain (38.4%). Furthermore, 20.5% reported pain in the mid spine region, 20.5% in the knees and legs, and 9.8% in the hands and feet. Multiple linear regression analyses showed that work-family conflict (p < 0.05) and interruptions (p < 0.05) significantly predicted lumbar and cervical pain in OR nurses, while influence at work (p < 0.05) only predicted lumbar pain. Conclusion: These results suggest that reducing the work-family conflict and interruptions at work, as well as offering opportunities to influence one's workplace, help to promote OR nurses' health.